PENGARUH ARUS KAS OPERASI DAN VOLATILITAS PENJUALAN TERHADAP PERSISTENSI LABA PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016 - 2020 (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to determine the operating cash flow and sales volatility variables on earnings persistence. The purpose of this study is to determine how much influence operating cash flow and sales volatility have on earnings persistence in Property and Real Estate companies listed on the Indonesia Stock Exchange 2016-2020. This type of research is quantitative. The data analysis technique used is panel data regression with a time series of 6 (six) years, namely the 2016-2020 period and 20 (twenty) companies according to the criteria. From the results of simultaneous hypothesis testing (F test) operating cash flow and sales volatility simultaneously have a significant effect on the earnings persistence variable. Based on the results of the partial test (t test) operating cash flow has a positive and significant effect on earnings persistence, while sales volatility has no significant effect on earnings persistence.